Does Performance-Based Funding Work? A European Perspective - Jongbloed, Ben; de Gayardon, Ariane (International Higher Education, 2023)
Ever more systems globally are tying the distribution of core public funds to performance indicators and objectives. This article describes the landscape of performance-based funding in Europe and offers some insights into its positive impacts and unintended consequences. Using the experiences of European systems, it also provides some recommendations for systems considering implementing or expanding performance-based funding.